When the Brain Speaks Ambigously: Encephalitis of Encephalopathy - Yang Yang Endro Arjuna; Pricilla Yani Gunawan (Universitas Airlangga, 2026)
Highlight: Encephalitis can present atypically, with symptoms overlapping with other neurological disorders. Hyperglycemia may mimic encephalitis, causing seizures and hemianopia. Early steroids may improve suspected viral or autoimmune encephalitis. ABSTRACT Introduction: Encephalitis does not always exhibit the typical clinical triad and can manifest with a broad spectrum of symptoms that overlap with other neurological or systemic disorders. Additionally, supportive diagnostic tests, including cerebrospinal fluid analysis, may yield nonspecific findings, further complicating the diagnosis. Case: A 28-year-old man reported having a headache for 3 weeks, followed by cognitive impairment, short-term memory loss, right homonymous hemianopia, and recurrent focal seizures of the left face lasting 30 seconds without loss of consciousness for the past 2 weeks. On examination, the patient was alert, with no signs of nuchal rigidity or motor impairment; random blood glucose was 637 mg/dL, ketone level was 0.8 mmol/L, and ketonuria was present. Non-contrast and contrast-enhanced cranial CT, as well as electroencephalogram (EEG), revealed no abnormalities. Based on the entire clinical evaluation, the patient was diagnosed with hyperglycemia-induced encephalopathy. Despite initiation of hyperglycemia management, no clinical improvement was observed. Cerebrospinal fluid examination on the second day of admission revealed mononuclear-dominant pleocytosis, a protein concentration of 60 mg/dL, and a glucose level of 90.1 mg/dL. The patient received blind intravenous methylprednisolone three times daily, resulting in significant clinical improvement. Conclusion: Viral and autoimmune encephalitis are the most common etiologies, but overlapping clinical manifestations and limited diagnostic tools often complicate diagnosis. Hyperglycemia is typically associated with focal rather than generalized seizures and may cause visual disturbance that usually improves following metabolic normalization. In cases where diagnostic resources are limited and viral or autoimmune encephalitis is suspected, empiric corticosteroid therapy may be beneficial.